2013
DOI: 10.1002/adhm.201200365
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Noninvasive Monitoring of In Vivo Inflammatory Responses using a pH Ratiometric Fluorescence Imaging Probe

Abstract: It is often difficult to continuously monitor and quantify inflammatory responses in vivo. These dynamic responses however are often accompanied by specific pH changes. A new ratiometric optical pH probe is developed by combining pH-sensitive (CypHer5E) and pH-insensitive (Oyster800) fluorescent dyes into nanoparticles for in vivo optical imaging. By taking the ratio of fluorescence intensities at different wavelengths, these nanosized sensors provide excellent measurement capabilities, and unique mapping, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…3c and 3d). 99 These results support that pH imaging probes can be used to assess the potential impact (inflammatory responses and toxicity) of biomaterial implants on the surrounding tissues. Furthermore, pH ratiometric imaging probes can also be used to assess the microenvironment and health of transplanted cells in scaffolds for tissue engineering application.…”
Section: Imaging the Release Of Inflammatory Productssupporting
confidence: 62%
See 3 more Smart Citations
“…3c and 3d). 99 These results support that pH imaging probes can be used to assess the potential impact (inflammatory responses and toxicity) of biomaterial implants on the surrounding tissues. Furthermore, pH ratiometric imaging probes can also be used to assess the microenvironment and health of transplanted cells in scaffolds for tissue engineering application.…”
Section: Imaging the Release Of Inflammatory Productssupporting
confidence: 62%
“…The ability of the pH ratiometric probes for in vivo determination of degree of acidosis was then tested in ischemic kidney injury, tumorigenesis and foreign body reaction models. 99 Indeed, we found that there was a very good relationship between tissue acidosis (pH values 7.4) and inflammatory cell accumulation (based on histological analyses) (Figs. 3c and 3d).…”
Section: Imaging the Release Of Inflammatory Productsmentioning
confidence: 71%
See 2 more Smart Citations
“…27 250 µl of solution containing H 2 O 2 (6.0 mM) and IR750-NP-L012 probes (0.4mg/ml) were added into each well, and then these phantoms were placed between the solution and the emission light pathways during image collection. Using a Kodak In Vivo FX Pro System (Kodak, USA) (f/stop, 2.5; 4×4 binning), the chemiluminescence intensities were collected with an exposure time of 5 min, and the fluorescence intensities were recorded with an exposure time of 30 sec (excitation at 760 nm, emission at 830 nm).…”
Section: Methodsmentioning
confidence: 99%